Computational Diagnostics for Dielectric Barrier Discharge plasma - Khalaf, Thamir H; Abd Ali, Zainab D (Al-Nahrain Journal of Science, 2018)
The characteristics of electric discharge in a gap between two (parallel -plate) dielectric plates, which called dielectric barrier discharge (DBD), are studied for three dielectric materials Teflon, Glass and Silicon. The gap is filled with the argon gas in atmosphere pressure at ambient temperature. The separation of plates is 2 mm and each dielectric of 1mm thickness and 10 cm in diameter. A sinusoidal voltage 750 with 50 kHz frequency is applied to one of the dielectric plates, and the other plate is grounded. Fluid model (after solving Boltzmann equation) is used to simulate the discharge within the configuration.The simulation results are showed a good diagnostics for the characteristics of the dielectric barrier discharge, through studying properties of breakdown of the gas, such as ,electric potential and field distributions, electron density, mean electrons energy ,electrons and ions currents densities ,and the total plasma current density.